Lean Six Sigma green belt - Vanzant Stern, Terra; Boose, Cherokee (Packt Publishing, 2024)
The course begins with a comprehensive introduction to Lean Six Sigma, laying a solid foundation in process improvement basics and key concepts. You'll explore Lean Six Sigma metrics, core methodologies, and the Seven Tools of Quality, building a strong understanding of process optimization. The course focuses on practical skills and tools, including the DMAIC Model (Define, Measure, Analyze, Improve, Control), important graphs and charts, and real-world applications. You'll learn to identify and eliminate waste, understand customer requirements (CTQs), and optimize processes for better quality and efficiency. As you progress, the course covers advanced topics like process control, root cause analysis, and statistical analysis techniques. You'll gain hands-on experience applying Lean Six Sigma principles to real projects, making data-driven decisions, and achieving tangible improvements. The course wraps up with a review of key concepts and a practical guide to implementing Lean Six Sigma methodologies in your organization. By the end, you'll be well-equipped to earn your Green Belt certification and drive process excellence in any industry. What you will learn Learn Process Improvement with Lean Six Sigma Apply DMAIC methodology for effective problem-solving Utilize the Seven Tools of Quality for defect reduction Understand core Lean Six Sigma concepts and terms Analyze data and identify opportunities for process optimization Implement statistical tools and techniques for quality improvements Audience This course is ideal for professionals seeking to enhance their process improvement skills and earn a Lean Six Sigma Green Belt certification. A basic understanding of business processes is recommended. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Terra Vanzant Stern, Phd: Dr Stern is a Six Sigma Master Black Belt and the principal of SSD Global Solutions, Inc. She has written several books and articles on problem solving, process improvement and leadership. Her most recent book, Lean and Agile Project Management was released as a second edition in May 2020. Cherokee Boose: Cherokee started as a computer technician and moved to a network administrator role. Her love for learning is what pushed her towards a career in IT education. Certifications: MCSE Cloud Platform and Infrastructure; MCSA: Server 2012; MCT; MCP; MTA: Networking Fundamentals; MTA: Windows Operating System Fundamentals; Six Sigma Green Belt; CompTIA A+, A+ CE, Network+, CTT+, and Cloud+.